THE DIFFERENCE BETWEEN COMPOUND WORDS AND WORD GROUPS - N.T.Kamoldinova (TADQIQOTLAR, 2025)
Abstract. This article examines the distinction between compound words and word groups, focusing on their structural, semantic, and grammatical properties. Although both involve multiple words, compound words function as single lexical items, while word groups remain syntactically flexible. This study highlights the defining features of each, including semantic unity, orthography, stress patterns, and grammatical behavior. Examples and insights from morphological and syntactic research help clarify the differences and address challenges in borderline cases. Understanding these differences is essential for language learners, linguists, and educators alike.